Secure and Distributed On-Demand Randomized Routing in WSN (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Security and energy efficiency is of paramount importance in a wireless sensor network. This is due to their vulnerabledeployment conditions and battery based power. This paper presents a secure and distributed algorithm that generatesroutes on-demand in a wireless sensor network. Dynamic route generation is facilitated by PSO, a metaheuristictechnique. Current network traffic in that route and charge contained in the candidate node are used as evaluationparameters along with the node distance, hence a huge reduction in the packet loss was observed. Experiments wereconducted and it was observed that the proposed algorithm exhibits very low selection overhead and also providesdistributed routs, which eventually lead to prolonged network lifetime.